SPIN STATES AND BREAKDOWN ENERGY OF ZnO DOPED WITH Fe³⁺: A SPIN-POLARIZED DFT+U STUDY (Universal International Scientific Journal, 2026)
In this paper, the spin states and band gap energy changes resulting from substitutional doping of Fe³⁺ ions in the wurtzite ZnO crystal lattice were studied using the spin-polarized DFT+U method. The calculations showed that the high-spin configuration of Fe³⁺ ions (3d⁵, S = 5/2) is energetically stable. The strong hybridization between the Fe 3d and O 2p orbitals creates an exchange separation (~2–3 eV) and forms additional impurity states in the band gap. As a result, the effective band gap narrows and the optical and magnetic properties of the material change significantly. The obtained results indicate that Fe-doped ZnO is promising in the fields of spintronics and photocatalysis.
Keywords: ZnO; Fe³⁺ doping; spin state